Ethnography : a theoretically oriented practice - Matera, Vincenzo; Biscaldi, Angela (Palgrave Macmillan, 2021)
This volume presents both a historical exploration of ethnography and a thematic discussion of major trends that, over different periods, have oriented and re-oriented research practice. As it overviews ethnography from different geographic and thematic perspectives, it further explores new lines of ethnographic research, including as feminist ethnography and visual research, that uncover non-traditional routes to anthropological knowledge.As the great ethnographer E. E. Evans-Pritchard wrote, "Anyone who is not a complete idiot can do fieldwork... but will [his contribution] be to theoretical, or just to factual knowledge?" As Evans-Pritchard highlights and as this book argues, successful ethnography must be connected to a sophisticated theoretical reflection rooted in social and cultural anthropology.
Keywords: Bourdieu, Pierre, : 1930-2002; Clifford, James, : 1945-; De Martino, Ernesto, : 1908-1965; Geertz, Clifford; Griaule, Marcel, : 1898-1956; Malinowski, Bronislaw, : 1884-1942; Marcus, George E; Radcliffe-Brown, A. R : (Alfred Reginald), : 1881-1955; Tedlock, Barbara; Tedlock, Dennis, : 1939-2016; Ethnology; Ethnology : History; Ethnology : Research; etnografia; kenttätyö; antropologia; kansatiede; oppihistoria; tutkimushistoria; antropologit